Productivity of groundnut (Arachis hypogaea L.) as influenced by varieties and plant densities: PRODUCTIVITY OF GROUNDNUT AS INFLUENCED BY VARIETIES AND PLANT DENSITIES - H BHARGAVI; M SRINIVASA REDDY; S TIRUMALA REDDY; P KAVITHA; U VIJAYA BHASKAR REDDY; P V RAMESH BABU (Journal of Oilseeds Research, 2016)
A field experiment was conducted during rabi season to study the influence of different levels of plant densities on growth and yield parameters of groundnut varieties. The experiment was conducted with three varieties and four levels of plant densities replicated thrice. Among the varieties, TCGS-29 (Narayani) significantly produced tallest plants over K6 and TAG-24. LAI of the varieties was not significant except at 60 days after sowing (DAS). At 60 DAS, significantly the highest LAI was recorded with K6 and the lowest was recorded with TAG-24. The drymatter produced by TAG-24 was statistically lowest at 30 and 60 DAS. However the same variety produced significantly highest drymatter during harvest over the other varieties tested. For all the varieties tested, the plant height was most influenced by different plant densities. However, the LAI and dry matter production significantly increased with increased population levels. With regard to pod production, haulm yield and harvest index all the varieties produced statistically similar yield. However, variation in density of planting resulted in production ofsignificantly lower podyield with 33.3 plants/m2 and the rest of the treatments produced statistically equal yield. However, superior haulm yield was recorded with 66.6 plants/m2.